Analisis Penerapan Program Kartu Petani Berjaya di Desa Gunung Mekar Kabupaten Lampung Timur - salam, fitriana aulia; Herowandi, Muhammad; Mosshananza, Hinfa (Universitas Muhammadiyah Lampung, 2024)
The research aims to describe the problems of implementing the Farmer’s Card Program in Gunung Mekar Village. This research is motivated by the fact that Indonesia is a country that is known as an agricultural country, that is , a country with an average population working as farmers. The method used is a qualitative research method, namely an analysis based on data obtained through interviews, observation and documentation. The result of the researchers are that the implementation of the Farmer’s Card Program in Gunung Mekar Village is not yet fully effective after being measured by three indicators are the existence of programs implemented, the existence of target groups, the existence of organizational or group implementation. The inhibiting factors in implementing the Farmer’s Card Program in Gunung Mekar Village are the lack of infrastructure and inadequate human resources for farmers.